Leading transformational change: Leveraging culture to create safe, healthy, and respectful workplaces - Junida, Isma; Marta, Rustono Farady; Panggabean, Hana; Salim, Mufid; Engliana, Engliana (Manajemen Komunikasi, 2025)
As a key player in the infrastructure sector, the organization's dedication to Occupational Safety and Health (OHS) is exemplified by the Corporate Life Saving Rule (CLSR) and various promotional activities, including the SHE Learn & Share Series SIG, commonly referred to as "SELARAS." SELARAS, a significant component of the promotional efforts, features prominent representatives from the top management of all company entities delivering impactful messages regarding the importance of OHS compliance. This study aimed to explore management statements contained in the SELARAS 2024 activities as a discourse that has the power to influence employees to present a safe, healthy, and respectful workplace environment. The research method used in this study is qualitative with Van Dijk’s critical discourse analysis. The data collection process, as conveyed by top management representatives in the 2024 SELARAS activities, was analyzed using critical discourse, which includes text analysis, social context, and social cognition through cultural dimensions. The result of the study explains that the messages contained in the SELARAS documentation describe the values, beliefs, and assumptions of the organization in all cultural dimensions in building a healthy, safe, and respectful workplace. This study shows the practical efforts of top management discourse in the SELARAS program to convey organizational values and foster a positive safety culture, aligning with the organization’s commitment to OHS excellence and respectful workplace policies.